Learning Trigonometry Using GeoGebra Learning Module: Are Under Achiever Pupils Motivated? (Sains Humanika, 2017)
Under achiever pupils were found to have low motivation level in learning mathematics. Pupils avoid Trigonometry and consider this topic as tough for them to master. The objective of this research is to measure under achiever motivation level towards Teaching and Learning (T&L) Trigonometry II topic using GeoGebra Learning Module (GLM). This research has used explanatory mixed methods which is survey and interview to answer the research questions. Pupils were exposed to GLM in Trigonometry II topics for a duration of two weeks. Motivation level are measured using questionnaire adapted from Instructional Material Motivational Scale (IMMS). Five pupils then were interviewed by the researcher to gauge pupils motivation towards GLM. Respondents are from 21 under achiever pupils from one intact class in Muar, Johor. Data analysis showed overall pupils’ motivation level are high (M = 4.16, SD = .279). The level of motivation of pupils for each subscale in ascending order is the Confidence (M = 3.92, SD = .268), Relevant (M = 4.07, SD = .357), Attention (M = 4.25, SD = .320), and Satisfaction (M = 4.50, SD = .436). Girls are significantly motivated [t (19) = 2,401, p
Keywords: Under Achiever; trigonometry; GeoGebra; motivation